PO067 Nitroglycerin triggering as a human migraine model in clinical research. (1st December 2017) - Karsan, Nazia; Bose, Pyari; Thompson, Charlotte; Goadsby, Peter
Abstract : Studying human migraine has challenges; namely capturing spontaneous attacks. Exogenous triggering has been developed, with substances such as nitroglycerin (NTG), to overcome some of these challenges and enable attacks to be studied in a predictable and reproducible fashion. We aimed to study NTG triggering of migraine attacks, with a view to phenotyping these compared to spontaneous attacks and imaging them using functional MRI. Subjects were screened and recruited following a migraine history and informed consent (n=49). Each subject was exposed to a 0.5 mcg/kg/min over 20 min NTG infusion. The phenotype of migraine symptomatology following triggering was documented. The association between baseline migraine diagnosis (episodic vs. chronic) and effectiveness of NTG triggering migraine headache was analysed using the Chi-squared test. p<0.05 was considered significant. The monthly baseline headache frequency ranged from 0–22 days (median=8). Migraine headache was successfully triggered in 40 subjects (82%). There was a trend towards a statistically significant association (p=0.061) between effective triggering and chronic migraine versus episodic. All 9 subjects who did not trigger a headache had episodic migraine with monthly headache days ranging from 0–10. NTG is an effective migraine trigger. Successful triggering may be related to a threshold effect, associated with baseline headache frequency.